Conformal mapping of doubly connected regions onto a disc with a circular slit by using an integral equation method via the Neumann Kernel - Ali Hassan Mohamed Murid, author; Hu, Laey Nee, 1972-, author; Mohd. Nor Mohamad, 1960-, author; Prosiding Seminar Kebangsaan Aplikasi Sain dan Matematik (2007 : Johor) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL